2000
DOI: 10.2527/2000.781224x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental degradable intake protein on utilization of medium- to low-quality forages.

Abstract: Three independent experiments were conducted each using 16 ruminally fistulated beef steers fed bermudagrass (8.2% CP, 71% NDF; Exp. 1), bromegrass (5.9% CP, 65% NDF; Exp. 2), or forage sorghum (4.3% CP, 60% NDF; Exp. 3) hays to evaluate the effects of increasing level of supplemental degradable intake protein (DIP) on forage utilization. In each experiment, steers were blocked by weight and assigned to one of four treatments, and hay was offered to each steer at 130% of average voluntary intake for the preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2
24

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 14 publications
7
53
2
24
Order By: Relevance
“…Increases in voluntary intake as a function of supplementation with nitrogenous compounds were also observed by Hannah et al (1991), Mathis et al (2001), Köster et al (2002), and Ortiz-Rubio et al (2007) in cattle fed low-quality forage.…”
Section: Resultsmentioning
confidence: 52%
“…Increases in voluntary intake as a function of supplementation with nitrogenous compounds were also observed by Hannah et al (1991), Mathis et al (2001), Köster et al (2002), and Ortiz-Rubio et al (2007) in cattle fed low-quality forage.…”
Section: Resultsmentioning
confidence: 52%
“…Fórmula dos suplementos (base úmida) utilizados nos tratamentos (T1 a T5) e composição bromatológica mé-dia, em porcentagem, de proteína bruta (PB), equivalente protéico em nitrogênio não protéico (EPNNP) e uréia, e nível de suplementação em porcentagem do peso vivo (Oferta). Mathis et al (2000), que ao suplementar com teores crescentes de proteína degradável no rúmen (0, 0,041, 0,082 e 0,124% PV) e utilizar feno de sorgo de baixa qualidade (4,3% PB e 59,5% FDN), obtiveram respostas lineares para a digestibilidade da FDN (DFDN), assim como para a digestibilidade da matéria orgânica (DMO). Koster et al (1997) obtiveram resposta quadrática para a DMO e tendência à resposta quadrática para a DFDN (p = 0,06), na substituição gradativa do nitrogênio suplementar, proveniente de uma fonte de proteí-na verdadeira, por uréia.…”
Section: Resultsunclassified
“…Provavelmente, as limitações provêm de características da forragem consumida (fermentabilidade inerente e disponibilidade da proteína) e da necessidade de proteína pelo animal (Koster et al, 1997;Mathis et al, 2000).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Protein supplements increase intake and utilization of low-quality forages in cattle (Kö ster et al, 1996), as do high-protein concentrates (Negesse et al, 2001) and leguminous forage (Osuji and Odenyo, 1997) supplementation to goats. However, it has been shown that protein supplements have little effect on feed intake of cattle consuming forages with CP concentrations above approximately 6% (Mathis et al, 2000). This number may be greater in growing goats whose minimum DM dietary protein concentration for maintenance is estimated at 6.0% to 8.5% depending on age (National Academies Press, 2007).…”
Section: Methodsmentioning
confidence: 99%